2015
DOI: 10.4236/ijmpcero.2015.41006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effectiveness of Diode Laser System (808 nm) versus Intense Pulse Light (IPL) in the Management of Unwanted Hair: A Split Face Comparative Study

Abstract: We have evaluated and compared the effectiveness of diode laser system (808 nm) and Intense Pulse Light (IPL) system (690-1200 nm) by studying the change in hair density, and the time of regrowth the hair. A total of 26 have completed three months' treatment, aged 16-50 years. Patients were treated by diode laser 808 nm and IPL 690-1200 nm devices. Pulse repetition rate for both was 1 Hz and short pulse width for diode laser and the IPL pulse width was 15 ms. The fluence was (33-41 and 30-41) J/cm 2 respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Average hair density at baseline was 69.1, which came down to 20.6 at 6 months [5] . HR-AL hamamy observed hair density to be 21.58±11.59 at baseline, 15.04±9.17 after 1 st session, 11.77±7.55 after 2 nd session, 8.96±6.77 after 3 rd session [6] . Similarly, in a study over 8 patients, approximate decrease in hair growth was from 75%-90% [7] .…”
Section: Discussionmentioning
confidence: 94%
“…Average hair density at baseline was 69.1, which came down to 20.6 at 6 months [5] . HR-AL hamamy observed hair density to be 21.58±11.59 at baseline, 15.04±9.17 after 1 st session, 11.77±7.55 after 2 nd session, 8.96±6.77 after 3 rd session [6] . Similarly, in a study over 8 patients, approximate decrease in hair growth was from 75%-90% [7] .…”
Section: Discussionmentioning
confidence: 94%
“…However, all of them used manual counting of hair from clinical pictures by blinded investigators. 2,3,[10][11][12][13] This can bring about intra-and inter-observer variation and cause observer fatigue which can adversely influence objectivity of the results. Hence, our study employed a truly objective, software-based method so as to overcome the above-stated limitation.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to objective methods of assessing the improvement carried out by other studies. However, all of them used manual counting of hair from clinical pictures by blinded investigators 2,3,10–13 …”
Section: Discussionmentioning
confidence: 99%
“…Also, diode laser procedure results in more post-treatment side effects like burn, hyperpigmentation, and erythema in comparison with IPL. Finally, AL-Hamamy et al observed a higher rate of patient satisfaction among those treated with IPL, compared to the diode laser, although the pain level associated with treatment through IPL resulted in more pain [21]. A large number of IPL devices exist; therefore, it is to some extent difficult to select appropriate parameters.…”
Section: Discussionmentioning
confidence: 99%